Problems with Cash and Other Non-Operating Assets Value in the Process of Valuing Company - Piotr Szczepankowski (Contemporary Economics)
In economic practice the process of valuing enterprises is based on potential earnings from companies operating assets ñ operating fixed assets and operating working capital. Cash and other non-operating assets (mainly financial) are treated as unproductive, non-income assets. Eventually, in process of pricing their current, accounting value is added to income value of enterprise or cash is treated as source for quick covering the debts of firm, what of course indirectly improve for better value of equity (the lower financial risk). Not taking into account the profitable influence of cash value and other non-operating assets can negatively affect on result of final value of enterprise, reducing it. In the article two alternative approaches (separate and inclusive) of cash value is presented. Also main determinants of estimating value of cash are described as well as potential threats of its valuation.